1974
DOI: 10.1007/bf00035885
|View full text |Cite
|
Sign up to set email alerts
|

The relative contributions of yield components to lint yield of upland cotton, Gossypium hirsutum L.

Abstract: Stepwise regression analyses provided an estimate of the net effect of yield components on lint yield of Upland cotton. Data from strain tests in the Pee Dee, South Carolina, cotton breeding program for crop years 1968 and 1969 were used in these analyses. Lint yield/m2 was the dependent variable. Independent variables were: bolls/m*, lint/seed, and seeds/boll.Correlation analyses indicated the relationships among yield components. Partial correlation coefficients were utilized to show the order of variable ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 5 publications
5
71
0
3
Order By: Relevance
“…Boll picking was performed over three time intervals and bolls picked from each plant were used to determine boll weight (BW), seeds per boll (SB), lint weight (LW), ginning out turn (GOT), lint index (LI), seed index (SI), seed cotton/seed (SCS), seed weight/seed (SWS), lint/seed (LS), and seed cotton yield/plant (YP). Worley et al (1974)'s method was used to calculate the seed cotton/seed (SCS), seed weight/ seed (SWS), and lint/seed (LS). The seed index was the weight of 100 seeds and the lint index was the lint obtained from 100 seeds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boll picking was performed over three time intervals and bolls picked from each plant were used to determine boll weight (BW), seeds per boll (SB), lint weight (LW), ginning out turn (GOT), lint index (LI), seed index (SI), seed cotton/seed (SCS), seed weight/seed (SWS), lint/seed (LS), and seed cotton yield/plant (YP). Worley et al (1974)'s method was used to calculate the seed cotton/seed (SCS), seed weight/ seed (SWS), and lint/seed (LS). The seed index was the weight of 100 seeds and the lint index was the lint obtained from 100 seeds.…”
Section: Methodsmentioning
confidence: 99%
“…A high level of heterosis has been reported in both intraspecific and interspecific hybrids of cotton for lint yield and yield components (Marani, 1967;Cole et al, 2009). Boll number is reported to be a major yield component, which affects hybrid yield (Worley et al, 1974;Zeng and Wu, 2012). In some cases, yield heterosis is associated with both boll weight and boll number (Marani, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Seed volume and seed density are important for an increase in seed vigor and thereby influence seed cotton yield (Ferguson and Turner, 1971). Worley et al (1974) reported that the boll number per unit of land area is an important factor for increasing the yield, followed by seeds per boll and lint weight per seed. Culp and Harrell (1975) stated that a higher lint percentage supports higher lint yield and that lint yield is influenced by the selection of boll size and seed size.…”
Section: Introductionmentioning
confidence: 99%
“…Lint yield is determined by bolls per square meter, seeds per boll, and lint per seed (Worley et al, 1974;Worley et al, 1976). Although the yield component, bolls per square meter, is an inherited trait, it is highly depended on plant density, and environmental effects on this component are large (Meredith and Bridge, 1973).…”
Section: Gene Action and Combining Ability For Lint Yield And Fiber Qmentioning
confidence: 99%